THE EFFECT OF PARTIAL REPLACEMENT OF ANIMAL PROTEIN WITH DUCKWEED GROWN IN THE TREATMENT UNIT OF THE NINEVEH PHARMACEUTICAL FACTORY WATER ON THE GROWTH PERFORMANCE OF COMMON CARP Cyprinus carpio L. FISH - Nidhal Al-Taee; Mahmoud Mohammad; Abdullah Abdul-Majeed (Mesopotamia Journal of Agriculture)
Duckweed grown in the water treatment unit of the Nineveh Pharmaceutical Factory contribute to reducing the level of pollution, and are used as a partial substitute for animal protein in common carp fingerling diets, in a growth experiment that lasted for 56 days, where the replacement rates reached 16.67, 33.33, and 50%, that is, a replacement rate, 0%, 2.6%, 5.2%, and 7.8% for treatments T1, T2, T3, and T4 of the total diet, respectively. The results of the statistical analysis showed that the fishes that fed the third diet were significantly superior (P≤0.05) to the other experimental diets in terms of criteria, final weight, total growth, daily gain, relative and specific growth rate, feed intake, feed conversion ratio, feed efficiency ratio, and protein efficiency ratio compared to the control treatment. The results showed that the highest percentage of pollutant removal from the water cleared from the treatment unit was in the spring season, which was represented by both total solids and phosphate compared to the winter and autumn seasons, while the highest percentage of nitrates was in the autumn season. It is clear from what was mentioned above that it is possible to partially replace duckweed with animal protein and that it is effective in reducing pollution of the water discharged from the process unit of the pharmaceutical factory.